ANALYSIS OF MEASURES OF GOVERNMENTAL SUPPORT IN THE INDUSTRY IN RUSSIA - E. Chirkina (Publishing House of the State University of Management, 2017)
This article analyzed governmental support in the automotive industry in the Russian Federation. It analyzed the strategy of the development of industry up until 2020, it also looked at the dynamics of investments and the volume of governmental support in the automotive industry. The main issues that affect the effectiveness of the governmental support of the industry were discovered. The results of this analysis can be used to further develop core solutions to improving the measures of support in the automotive industry in Russia.